Negative current collector and preparation method thereof, negative pole piece, solid-state lithium battery and vehicle

By using carbonized metal organic frame material and zeolite imidazole ester skeleton material as functional coatings in lithium-free negative electrode current collector, the problem of poor lithium depositing during charging of lithium batteries in lithium batteries is solved, and the electrochemical performance is improved and Safety reduces the nucleation probability of lithium dendrites.

CN119208618APending Publication Date: 2024-12-27CHONGQING CHANGAN AUTOMOBILE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411374766.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The lithium-friendly effect of existing lithium-free negative electrode current collectors is poor, resulting in poor lithium depositing uniformity during charging, which can easily cause lithium dendrites to grow and internal short circuits, and the negative electrode current collector may have side reactions, reducing electrochemical performance.

Method used

Carbonized metal organic frame material is used as functional coating, and lithium-philic materials are installed on the surface, including zeolite imidazole ester skeleton material and foam copper as current collector substrates. The negative electrode current collector is prepared through ultrasonic treatment and heat treatment to improve the uniformity of lithium sedimentation and electricity. Chemical properties.

Benefits of technology

It improves the lithium sedimentation uniformity and electrochemical performance of the negative electrode current collector, reduces the nucleation and growth probability of lithium dendrites, enhances the safety and energy density of lithium batteries, and adapts to a wider operating temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208618A_ABST
    Figure CN119208618A_ABST
Patent Text Reader

Abstract

The invention provides a negative current collector and a preparation method thereof, a negative pole piece, a solid-state lithium battery and a vehicle, and relates to the field of lithium batteries. The negative current collector comprises a current collector substrate; the functional coating is arranged on at least part of the surface of the current collector substrate, the functional coating comprises a carbonized metal organic framework material, and a lithium-loving material is arranged on the surface of the metal organic framework material. Therefore, the lithium-loving material is arranged on the metal organic framework material on the surface of the negative electrode current collector, so that the lithium deposition uniformity on the negative electrode current collector can be improved, the lithium battery has better safety and battery energy density, and in addition, the metal organic framework material on the surface of the negative electrode current collector has better chemical stability, mechanical strength, thermal stability and conductivity, so that the lithium battery can be used for lithium ion batteries. The electrochemical performance, the mechanical strength, the working temperature width and the battery energy density of the lithium battery can be correspondingly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a negative electrode current collector and a preparation method thereof, a negative electrode pole piece, a solid-state lithium battery, and a vehicle. Background Art

[0002] Compared with lithium metal negative electrodes, lithium-free negative electrodes have higher energy density and safety performance, and avoid the use of lithium metal. The working principle of lithium-free negative electrodes is: during the charging process of lithium batteries, lithium ions will migrate to the surface of the negative electrode current collector and combine with electrons to deposit lithium metal; during the discharge process of lithium batteries, the lithium metal deposited on the negative electrode current collector will dissolve and the lithium metal will return to the positive electrode.

[0003] As a key component of lithium-free negative electrode, negative electrode current collector has a vital impact on the electrochemical performance of lithium battery. However, due to the poor lithium affinity of current negative electrode current collector, the uniformity of lithium deposition on negative electrode current collector is poor during the charging process of lithium battery, which may cause lithium metal aggregation on negative electrode current collector, easily lead to lithium dendrite growth, and even cause internal short circuit of lithium battery in severe cases; in addition, negative electrode current collector may also have side reactions, which will make it difficult for positive electrode to fully receive lithium ions during charging process, and dead lithium deposition is easy to form on positive electrode, which will reduce the electrochemical performance of lithium battery. Summary of the invention

[0004] The present application provides a negative electrode current collector and a preparation method thereof, a negative electrode pole piece, a solid-state lithium battery, and a vehicle. In this way, the metal organic framework material on the surface of the negative electrode current collector is provided with a lithium-philic material, which can improve the uniformity of lithium deposition on the negative electrode current collector, and the lithium battery has better safety and battery energy density. In addition, the metal organic framework material on the surface of the negative electrode current collector has better chemical stability, mechanical strength, thermal stability and conductivity, which can correspondingly improve the electrochemical performance, mechanical strength, operating temperature range and battery energy density of the lithium battery.

[0005] The technical solution of this application is as follows:

[0006] According to the first aspect of the present application, there is provided a negative electrode current collector, comprising: a current collector substrate; a functional coating, the functional coating being arranged on at least a portion of the surface of the current collector substrate, the functional coating comprising a carbonized metal-organic framework material, and a lithium-philic material being arranged on the surface of the metal-organic framework material.

[0007] According to the above technical means, the functional coating of the carbonized metal organic framework material is arranged on at least part of the surface of the current collector substrate. During the charging process of the lithium battery, the lithium-philic material on the surface of the metal organic framework material can attract lithium ions near the negative electrode current collector to achieve lithium plating (that is, the lithium plating process is mainly carried out at the position where the lithium-philic material is located), which is conducive to achieving a uniform distribution of current density in the negative electrode current collector, improving the uniformity of lithium deposition on the negative electrode current collector, reducing the probability of nucleation and growth of lithium dendrites, and reducing the probability of lithium dendrite growth causing short circuit phenomenon in the lithium battery. It can also ensure the capacity of the lithium-free negative electrode, so that the lithium battery has better safety and battery energy density. In addition, the carbonized metal organic framework material has better chemical stability, mechanical strength, thermal stability, and electrical conductivity, including the functional coating of the carbonized metal organic framework material is arranged on at least part of the surface of the current collector substrate, therefore, the chemical stability, mechanical strength, thermal stability, and electrical conductivity of the negative electrode current collector can be correspondingly improved, and the electrochemical performance, mechanical strength, operating temperature width, and battery energy density of the lithium battery can be correspondingly improved.

[0008] In a possible implementation, the metal organic framework material includes a zeolite imidazolate framework material, the zeolite imidazolate framework material includes coordinated imidazolate ions and lithium-philic metal ions, and the lithium-philic material includes lithium-philic metal ions.

[0009] According to the above technical means, due to the lithium-philic metal ions (such as Zn 2+ ) has good lithium affinity, and the lithium-affinity metal ions can attract lithium ions near the negative electrode current collector to achieve lithium plating (that is, the lithium plating process is mainly carried out at the location of the lithium-affinity metal ions), which is conducive to achieving uniform distribution of current density in the negative electrode current collector, improving the uniformity of lithium deposition on the negative electrode current collector, thereby reducing the probability of nucleation and growth of lithium dendrites, and is conducive to reducing the probability of lithium dendrite growth causing short circuit phenomena in lithium batteries, and can also ensure the capacity of lithium-free negative electrodes. Lithium batteries have better safety and battery energy density. Zeolite imidazolate framework materials also have the advantages of excellent specific surface area, excellent pore size distribution, etc., which are conducive to improving the uniformity of lithium deposition on the negative electrode current collector, thereby reducing the probability of nucleation and growth of lithium dendrites.

[0010] In addition, the imidazolate ions and lithium-philic metal ions in the zeolite imidazolate framework material are coordinated through ionic bonds, so that the zeolite imidazolate framework material has a stable lattice structure. Therefore, the zeolite imidazolate framework material has excellent chemical stability, mechanical strength, thermal stability, and conductivity, which can correspondingly improve the chemical stability, mechanical strength, thermal stability, and conductivity of the negative electrode collector, and correspondingly improve the electrochemical performance, mechanical strength, operating temperature range, and battery energy density of the lithium battery.

[0011] In a possible embodiment, the lithium-philic metal ion includes at least one of zinc ion, silver ion, magnesium ion, aluminum ion and tin ion. Preferably, the lithium-philic metal ion is zinc ion.

[0012] According to the above technical means, the above lithium-philic metal ions have a higher lithium affinity and can significantly improve the lithium affinity effect of the negative electrode current collector.

[0013] In one possible embodiment, the current collector substrate includes copper foam.

[0014] According to the above technical means, the above-mentioned current collector substrate includes a copper foam with a three-dimensional structure. The copper foam with a high surface area can provide abundant internal space for setting functional coatings, increase the setting area of ​​lithium-philic materials, and is beneficial to adjusting the lithium ion transmission electric field, improving the uniformity of the effective current density in the negative electrode current collector, and reducing the hidden danger of nucleation and growth of lithium dendrites due to uneven effective current density; the copper foam with a high surface area can also adjust the nucleation sites of lithium metal on the current collector substrate, shorten the mass transfer distance of lithium ions, improve the uniformity of lithium deposition on the negative electrode current collector, and inhibit the volume change of the negative electrode current collector.

[0015] In addition, the conductivity of copper foam is poor. Since the carbonized metal-organic framework material has excellent conductivity, including the functional coating of the metal-organic framework material set on at least part of the surface of the copper foam, the negative electrode current collector provided in the embodiment of the present application can take into account both excellent conductivity and uniform lithium deposition effect.

[0016] In one possible implementation, the pore size of the metal organic framework material is 0.5 nanometers to 1.2 nanometers.

[0017] According to the above technical means, the pore size of the metal organic framework material is controlled within the above range, which is beneficial for the metal organic framework material to selectively adsorb and separate lithium ions to achieve lithium insertion during the charging process of the lithium battery and lithium removal during the discharging process of the lithium battery.

[0018] In a possible implementation, the thickness of the functional coating is 0.3 micrometer to 0.8 micrometer.

[0019] According to the above technical means, the functional coating has better lithium ion adsorption capacity and better thickness uniformity, and the lithium battery has better battery energy density.

[0020] In a possible implementation manner, the functional coating further includes carbonized carbon material.

[0021] According to the above technical means, the carbonized carbon material can increase the conductivity of the functional coating, thereby increasing the conductivity of the negative electrode current collector.

[0022] According to the second aspect provided by the present application, a method for preparing a negative electrode current collector is provided, comprising: mixing a current collector substrate, a metal organic framework material and a carbon source solution to obtain a mixture; heat treating the mixture to obtain a negative electrode current collector; wherein a lithium-philic material is provided on the surface of the metal organic framework material.

[0023] In one possible embodiment, the current collector substrate includes copper foam.

[0024] In a possible embodiment, the metal organic framework material includes a zeolite imidazolate framework material, and the lithium-philic material includes a lithium-philic metal ion in the zeolite imidazolate framework material. For example, the lithium-philic metal ion includes at least one of zinc ion, silver ion, magnesium ion, aluminum ion and tin ion.

[0025] In a possible embodiment, the carbon source solution includes at least one of glucose solution, ethylene glycol, glycerol and furfuryl alcohol.

[0026] In a possible implementation manner, the molar ratio of the carbon source solution to the metal organic framework material is (0.8-1.2):1.

[0027] In one possible embodiment, the mixing treatment includes: ultrasonically treating the current collector substrate, the carbon source solution and the metal organic framework material, filtering after standing to obtain a mixture; wherein the power of the ultrasonic treatment is 120W to 300W, and the time of the ultrasonic treatment is 1h to 3h.

[0028] In a possible implementation manner, the heat treatment temperature is 350° C. to 650° C., and the heat treatment time is 2 h to 5 h.

[0029] In a possible embodiment, the method for preparing the zeolite imidazolate framework material comprises: in a solvent, 2-methylimidazole and a metal source material are subjected to a coordination reaction to obtain the zeolite imidazolate framework material. For example, the metal source material can be at least one of a zinc source material, a silver source material, a magnesium source material, an aluminum source material, and a tin source material.

[0030] In some examples, the zinc source material includes at least one of zinc nitrate hexahydrate and zinc acetate dihydrate. In some examples, the silver source material includes silver nitrate. In some examples, the magnesium source material includes magnesium nitrate. In some examples, the aluminum source material includes aluminum nitrate. In some examples, the tin source material includes tin nitrate.

[0031] In a possible implementation, the molar ratio of 2-methylimidazole to the metal source material is (0.8-1.2):(0.8-1.2).

[0032] According to a third aspect provided by the present application, a negative electrode plate is provided, and the negative electrode plate includes the negative electrode current collector of the above embodiment, or the negative electrode current collector prepared by the above method for preparing the negative electrode current collector.

[0033] According to the fourth aspect provided by the present application, a solid-state lithium battery is provided, which includes a positive electrode plate, a solid electrolyte membrane, and a negative electrode plate of the above embodiment, wherein the solid electrolyte membrane is located between the positive electrode plate and the negative electrode plate.

[0034] According to a fifth aspect provided by the present application, a vehicle is provided, comprising the solid-state lithium battery of the above embodiment.

[0035] Therefore, the above technical features of the present application have the following beneficial effects:

[0036] (1) In the above-mentioned negative electrode current collector, the functional coating of the carbonized metal organic framework material is arranged on the surface of the current collector substrate. During the charging process of the lithium battery, the lithium-philic material on the surface of the metal organic framework material can attract lithium ions near the negative electrode current collector to achieve lithium plating, which is conducive to achieving a uniform distribution of current density in the negative electrode current collector, improving the uniformity of lithium deposition on the negative electrode current collector, reducing the probability of nucleation and growth of lithium dendrites, and reducing the probability of lithium dendrite growth causing short circuit phenomenon in the lithium battery. It can also ensure the capacity of the lithium-free negative electrode, so that the lithium battery has better safety and battery energy density. In addition, the carbonized metal organic framework material has better chemical stability, mechanical strength, thermal stability, and electrical conductivity. The functional coating of the carbonized metal organic framework material is arranged on the surface of the current collector substrate. Therefore, the chemical stability, mechanical strength, thermal stability, and electrical conductivity of the negative electrode current collector can be correspondingly improved, and the electrochemical performance, mechanical strength, operating temperature range, and battery energy density of the lithium battery can be correspondingly improved.

[0037] (2) In the above-mentioned negative electrode current collector, the metal organic framework material includes a zeolite imidazolate skeleton material, the zeolite imidazolate skeleton material includes a coordinated imidazolate ion and a lithium-philic metal ion, and the lithium-philic material includes a lithium-philic metal ion (the lithium-philic metal ion includes at least one of zinc ion, silver ion, magnesium ion, aluminum ion and tin ion). Since the lithium-philic metal ion (such as zinc ion) has good lithium affinity, the lithium-philic metal ion can attract lithium ions near the negative electrode current collector to achieve lithium plating, which is conducive to achieving a uniform distribution of current density in the negative electrode current collector, improving the uniformity of lithium deposition on the negative electrode current collector, and reducing the probability of lithium dendrite growth causing short circuit phenomenon in the lithium battery. It can also ensure the capacity of the lithium-free negative electrode, and the lithium battery has better safety and battery energy density. The zeolite imidazolate skeleton material also has the advantages of excellent specific surface area, excellent pore size distribution, etc., which is conducive to further improving the uniformity of lithium deposition on the negative electrode current collector and reducing the probability of nucleation and growth of lithium dendrites.

[0038] In addition, the imidazolate ions and lithium-philic metal ions in the zeolite imidazolate framework material are coordinated through ionic bonds, so that the zeolite imidazolate framework material has a stable lattice structure. Therefore, the zeolite imidazolate framework material has excellent chemical stability, mechanical strength, thermal stability, and conductivity, which can correspondingly improve the chemical stability, mechanical strength, thermal stability, and conductivity of the negative electrode collector, and correspondingly improve the electrochemical performance, mechanical strength, operating temperature range, and battery energy density of the lithium battery.

[0039] (3) The current collector substrate provided in the embodiment of the present application includes a copper foam with a three-dimensional structure. The copper foam with a high surface area can provide abundant internal space for setting lithium-philic materials, which is beneficial to adjusting the lithium ion transmission electric field, improving the uniformity of the effective current density in the negative electrode current collector, and reducing the hidden danger of nucleation and growth of lithium dendrites due to uneven effective current density; the copper foam with a high surface area can also adjust the nucleation sites of lithium metal on the current collector substrate, shorten the mass transfer distance of lithium ions, improve the uniformity of lithium deposition on the negative electrode current collector, and inhibit the volume change of the negative electrode current collector.

[0040] In addition, the conductivity of copper foam is poor. Since the carbonized metal-organic framework material has excellent conductivity, including the functional coating of the metal-organic framework material set on at least part of the surface of the copper foam, the negative electrode current collector provided in the embodiment of the present application can take into account both excellent conductivity and uniform lithium deposition effect.

[0041] (4) The pore size of the metal organic framework material is 0.5 nanometers to 1.2 nanometers. Controlling the pore size of the metal organic framework material within the above range is conducive to the metal organic framework material selectively adsorbing and separating lithium ions to achieve lithium insertion during the charging process of the lithium battery and lithium removal during the discharge process of the lithium battery. The thickness of the functional coating is 0.3 micrometers to 0.8 micrometers. Controlling the thickness of the functional coating within the above range, the functional coating has better lithium ion adsorption and better thickness uniformity, and the lithium battery has better battery energy density.

[0042] It should be noted that the technical effects brought about by any implementation method in the second to fifth aspects can refer to the technical effects brought about by the corresponding implementation method in the first aspect, and will not be repeated here.

[0043] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the specification are used to explain the principles of the present application, and do not constitute an improper limitation on the present application.

[0045] Figure 1 is a scanning electron microscope image of some negative electrode current collectors according to an exemplary embodiment;

[0046] Figure 2 is another scanning electron microscope image of some negative electrode current collectors according to an exemplary embodiment. DETAILED DESCRIPTION

[0047] In order to enable ordinary persons in the art to better understand the technical solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.

[0048] With the booming development of industries such as electric vehicles, higher requirements have been placed on the energy density and other performance of lithium batteries. The current commercial lithium batteries with graphite anode systems have reached the bottleneck of their energy density. Lithium metal has excellent theoretical capacity (up to 3860mAhg -1 ) and low electrode potential (-3.04V vs. SHE), and is often used as the negative electrode active material of the negative electrode sheet of lithium batteries. Lithium metal negative electrodes mainly include ultra-thin lithium metal negative electrodes (the thickness of lithium metal is 20 microns or even lower) and high-load lithium metal negative electrodes. The problems with ultra-thin lithium metal negative electrodes include: the preparation technology of ultra-thin lithium metal negative electrodes is still immature, resulting in high preparation costs for ultra-thin lithium metal negative electrodes, which is not conducive to industrial production; the problems with high-load lithium metal negative electrodes include: high-load lithium metal negative electrodes require more lithium metal consumption, which is limited by the current shortage of lithium metal. Therefore, high-load lithium metal does not conform to the future development trend of lithium batteries, and high-load lithium metal negative electrodes are prone to safety hazards, and the corresponding lithium batteries have poor battery performance.

[0049] Compared with lithium metal negative electrodes, lithium-free negative electrodes have higher energy density and safety performance, and avoid the use of lithium metal, which is conducive to reducing the preparation cost of lithium batteries. The working principle of lithium-free negative electrodes is: during the charging process of lithium batteries, lithium ions will migrate to the surface of the negative electrode current collector and combine with electrons to deposit lithium metal (i.e. lithium insertion); during the discharge process of lithium batteries, the lithium metal deposited on the negative electrode current collector dissolves, and the lithium metal returns to the positive electrode (i.e. lithium desorption). The lithium-free negative electrode includes at least one of the following technical problems: (1) Since the lithium affinity of the negative electrode current collector is usually poor, during the charging process of the lithium battery, the uniformity of lithium deposition on the negative electrode current collector is poor, which may cause the lithium metal on the negative electrode current collector to aggregate, easily induce the growth of lithium dendrites, and even cause an internal short circuit of the lithium battery in severe cases; (2) The negative electrode current collector may also undergo side reactions, which will make it difficult for the positive electrode to fully receive lithium ions during the charging process, and dead lithium deposits are easily formed on the positive electrode, which will reduce the electrochemical performance of the lithium battery; (3) During the charging process of the lithium battery, the negative electrode current collector may undergo structural expansion due to lithium insertion, which may easily affect the structural stability of the negative electrode current collector and the structural stability of the lithium battery.

[0050] In order to solve the above technical problems, the prior art has proposed some solutions. For example, in some solutions, a high entropy metal organic framework FeCoNiCuCd HEMOF-74 / C composite material can be prepared, and the composite material can be used as the negative electrode in a lithium-free negative electrode lithium metal battery to inhibit the formation of lithium dendrites and promote the generation of a homogeneous lithium layer; the existing problem is that the cost of the raw materials required to prepare the composite material is relatively high, especially the carbon paper required in the preparation process, and the carbon paper is fragile, easy to be affected by moisture, and the conductivity is greatly affected by factors such as temperature and pressure, so the composite material is difficult to achieve industrialization. In other solutions, a composite carbon nanofiber current collector can be used as the negative electrode current collector, and the composite carbon nanofiber current collector is a carbon fiber negative electrode material PNCF@ZnO rich in N and ZnO; the existing problem is that the composite carbon nanofiber current collector is not easy to achieve uniform deposition of lithium ions, and the preparation method is relatively complicated, and it is not easy to achieve industrialization.

[0051] Based on this, the embodiment of the present application proposes a vehicle, which can be a pure electric vehicle or a hybrid electric vehicle. In order to realize the basic functions of the vehicle, the vehicle may include a body, a chassis, a battery system and a power system. Of course, the vehicle may also include other components, which are only illustrative here and do not limit the specific composition of the vehicle.

[0052] The vehicle body may include a vehicle frame, doors and windows. The vehicle frame may form the overall shape of the vehicle exterior and form a seating space for accommodating passengers. The doors may be rotatably connected to the vehicle frame and may open or close the internal driving space. The windows may be mounted on the doors or the vehicle frame to facilitate passengers to observe the external environment. The chassis may include components such as a transmission system and a drive system. Among them, the drive system may drive the wheels to rotate. According to different driving modes of the drive system, the drive system may be divided into front-wheel drive, rear-wheel drive and four-wheel drive arrangements. The transmission system may transfer the power generated by the power system to the wheels. The power system may provide power for the vehicle so that the vehicle can complete basic driving functions. Depending on the type of vehicle, the composition of the power system may also be different. Exemplarily, when the vehicle is an electric vehicle, the power system may include an electric motor. In order to power the power system (such as an electric motor), the vehicle provided in the embodiment of the present application also includes a battery system, the battery system includes a lithium battery, and the lithium battery may be used to provide electrical energy. The lithium battery may be connected to the power system of the vehicle, so that the electrical energy of the battery pack may be transferred to the power system of the vehicle for powering.

[0053] From the above analysis, it can be seen that the poor uniformity of lithium deposition on the negative electrode current collector may cause the lithium metal on the negative electrode current collector to aggregate, triggering the growth of lithium dendrites, and the negative electrode current collector may also undergo side reactions, which will make it difficult for the positive electrode to fully receive lithium ions during the charging process, thereby forming dead lithium deposited on the positive electrode. Based on this, the embodiment of the present application provides a negative electrode current collector to improve the uniformity of lithium deposition on the negative electrode current collector, thereby improving the safety of lithium batteries and the battery energy density.

[0054] An embodiment of the present application provides a negative electrode current collector, which includes: a current collector substrate; a functional coating, the functional coating is disposed on at least a portion of the surface of the current collector substrate (for example, the functional coating can be disposed on the entire surface of the current collector substrate, and for another example, the functional coating can be disposed on a portion of the surface of the current collector substrate), the functional coating includes a carbonized metal organic framework material (MOF material), and the surface of the metal organic framework material is provided with a lithium-philic material (for example, the inner surface and the outer surface of the metal organic framework material can be provided with a lithium-philic material).

[0055] In the above-mentioned negative electrode current collector, a functional coating of a carbonized metal organic framework material is arranged on at least a portion of the surface of the current collector substrate, and a lithium-philic material is arranged on the surface of the metal organic framework material. During the charging process of the lithium battery, the lithium-philic material can attract lithium ions near the negative electrode current collector to achieve lithium plating (that is, the lithium plating process is mainly carried out at the location where the lithium-philic material is located). By controlling the distribution of the lithium-philic material, it is beneficial to achieve a uniform distribution of current density in the negative electrode current collector, improve the uniformity of lithium deposition on the negative electrode current collector, reduce the probability of nucleation and growth of lithium dendrites, and reduce the probability of lithium dendrite growth causing short circuit in the lithium battery. It can also ensure the capacity of the lithium-free negative electrode, so that the lithium battery has better safety and battery energy density.

[0056] In addition, the carbonized metal organic framework material has excellent chemical stability, mechanical strength, thermal stability, and electrical conductivity. Since the carbonized metal organic framework material has excellent chemical stability, including the functional coating of the carbonized metal organic framework material is set on at least part of the surface of the current collector substrate, the probability of side reactions of the negative electrode current collector (such as corrosion of the negative electrode current collector) can be reduced, and the amount of dead lithium in the positive electrode can be greatly reduced, which is beneficial to improving the electrochemical performance of the lithium battery; since the carbonized metal organic framework material has excellent mechanical strength, including the functional coating of the carbonized metal organic framework material is set on at least part of the surface of the current collector substrate, the mechanical strength of the negative electrode current collector can be improved, and the structural expansion of the negative electrode current collector due to lithium insertion can be suppressed. The carbonized metal organic framework material has excellent thermal stability, including the functional coating of the carbonized metal organic framework material on at least a portion of the surface of the current collector substrate, which can improve the high temperature stability of the negative electrode current collector, so that the lithium battery can adapt to a wider operating temperature; the carbonized metal organic framework material has excellent conductivity, including the functional coating of the carbonized metal organic framework material on at least a portion of the surface of the current collector substrate, which can improve the conductivity of the negative electrode current collector, and the lithium battery has excellent battery energy density.

[0057] In some embodiments, the metal organic framework material includes a zeolite imidazolate framework material (such as ZIF-8), the zeolite imidazolate framework material includes coordinated imidazolate ions and lithium-philic metal ions (for example, the lithium-philic metal ions include at least one of zinc ions, silver ions, magnesium ions, aluminum ions and tin ions), and the lithium-philic material includes a lithium-philic metal ion (such as zinc ions). Figure 1 , the functional coating includes a zeolite imidazolate framework material having a porous structure, reference Figure 2 The zeolite imidazolate framework material (ZIF-8) particles are coated on the surface of the current collector substrate, and the zeolite imidazolate framework material (ZIF-8) has high uniformity on the current collector substrate.

[0058] Since the lithium-philic metal ions (for example, the lithium-philic metal ions include at least one of zinc ions, silver ions, magnesium ions, aluminum ions and tin ions) have good lithium affinity, the lithium-philic metal ions (such as zinc ions) can attract lithium ions near the negative electrode current collector to achieve lithium plating (that is, the lithium plating process is mainly carried out at the location of the lithium-philic metal ions). By controlling the distribution of the lithium-philic metal ions in the zeolite imidazolate framework material, it is beneficial to achieve a uniform distribution of current density in the negative electrode current collector, improve the uniformity of lithium deposition on the negative electrode current collector, and thus reduce the probability of nucleation and growth of lithium dendrites, which is beneficial to reduce the probability of lithium dendrite growth causing short circuit phenomena in lithium batteries, and can also ensure the capacity of lithium-free negative electrodes. The lithium battery has better safety and battery energy density. In addition, the zeolite imidazolate framework material also has an excellent specific surface area (for example, the specific surface area can be as high as 1500m 2 / g) and excellent pore size distribution, which are beneficial to improving the uniformity of lithium deposition on the negative electrode current collector, thereby reducing the probability of nucleation and growth of lithium dendrites.

[0059] Furthermore, the imidazolate ions and the lithium-philic metal ions (such as zinc ions) in the zeolite imidazolate framework material (such as ZIF-8) are coordinated through ionic bonds, so that the zeolite imidazolate framework material has a stable lattice structure. Therefore, the zeolite imidazolate framework material has excellent chemical stability, mechanical strength, thermal stability, and electrical conductivity. Since the carbonized zeolite imidazolate framework material has excellent chemical stability, including the functional coating of the carbonized zeolite imidazolate framework material is arranged on at least part of the surface of the current collector substrate, the probability of side reactions (such as corrosion of the negative electrode current collector) of the negative electrode current collector can be reduced, and the amount of dead lithium in the positive electrode can be greatly reduced, which is beneficial to improving the electrochemical performance of the lithium battery; since the carbonized zeolite imidazolate framework material has excellent mechanical strength, including the functional coating of the carbonized zeolite imidazolate framework material is arranged on at least part of the surface of the current collector substrate, the mechanical strength of the negative electrode current collector can be improved, and the structural expansion of the negative electrode current collector due to lithium insertion can be suppressed. The invention discloses a novel lithium-ion battery having a lithium-ion battery and a lithium-ion battery having a lithium-ion battery. The lithium-ion battery has a lithium-ion battery and a lithium-ion battery having a lithium-ion battery. The lithium-ion battery has a lithium-ion battery and a lithium-ion battery having a lithium-ion battery. The lithium-ion battery has a lithium-ion battery and a lithium-ion battery having a lithium-ion battery. The lithium-ion battery has a lithium-ion battery and a lithium-ion battery having a lithium-ion battery. The lithium-ion battery has a lithium-ion battery and a lithium-ion battery having a lithium-ion battery. The lithium-ion battery has a lithium-ion battery and a lithium-ion battery having a lithium-ion battery.

[0060] In some embodiments, the current collector substrate includes copper foam.

[0061] In conventional schemes, flat copper foil is usually used as the current collector substrate. Due to the low specific surface area of ​​the flat copper foil, the negative electrode current collector corresponding to the flat copper foil may have a higher local current density, which may easily cause the nucleation and growth of lithium dendrites. In addition, defects such as microcracks or pits are prone to exist on the flat copper foil, which results in poor uniformity of lithium deposition on the negative electrode current collector.

[0062] Compared with a flat copper foil as a current collector substrate, the current collector substrate provided by the embodiment of the present application includes a foam copper with a three-dimensional structure. The foam copper with a high surface area can provide abundant internal space to set the functional coating (the functional coating can be set on the outer surface or inner surface of the foam copper), increase the setting area of ​​the lithium-philic material, adjust the lithium ion transmission electric field, improve the uniformity of the effective current density in the negative electrode current collector, and reduce the hidden danger of nucleation and growth of lithium dendrites due to uneven effective current density (for example, the effective current density in some areas of the negative electrode current collector is too large, while the effective current density in other areas is too small, which may cause the nucleation and growth of lithium dendrites in areas with excessive effective current density). In addition, the foam copper has a high surface area, which is conducive to adjusting the nucleation site of lithium metal on the current collector substrate, shortening the mass transfer distance of lithium ions, improving the uniformity of lithium deposition on the negative electrode current collector, and inhibiting the volume change of the negative electrode current collector.

[0063] Furthermore, the conductivity of copper foam is poor. Since the carbonized metal organic framework material has excellent conductivity, the functional coating of the metal organic framework material is set on at least part of the surface of the copper foam, so that the negative electrode current collector can take into account both excellent conductivity and uniform lithium deposition effect.

[0064] In some embodiments, the pore size of the metal organic framework material is 0.5 nanometers to 1.2 nanometers. For example, the pore size of the metal organic framework material can be 0.5 nanometers, 0.7 nanometers, 0.9 nanometers, 1.0 nanometers, or 1.2 nanometers.

[0065] The pore size of the metal organic framework material is controlled within the above range, and the pore size of the metal organic framework material is moderate, which is conducive to the metal organic framework material selectively adsorbing and separating lithium ions, so as to achieve lithium insertion during the charging process of the lithium battery and lithium removal during the discharge process of the lithium battery. In addition, it can alleviate the problem that the pore size of the metal organic framework material is too large, causing impurity ions to enter the pores of the metal organic framework material and occupy the sites of lithium ions, thereby reducing the battery energy density of the lithium battery, and it can also alleviate the problem that the pore size of the metal organic framework material is too small, causing lithium ions to be difficult to enter the pores of the metal organic framework material, affecting the lithium insertion during the charging process of the lithium battery and the lithium removal during the discharge process of the lithium battery.

[0066] In some embodiments, the thickness of the functional coating is 0.3 micrometer to 0.8 micrometer. For example, the thickness of the functional coating can be 0.3 micrometer, 0.4 micrometer, 0.5 micrometer, 0.6 micrometer, 0.7 micrometer, 0.8 micrometer.

[0067] By controlling the thickness of the functional coating within the above range, the thickness of the functional coating is moderate, the functional coating has better lithium ion adsorption and better thickness uniformity, and the lithium battery has better battery energy density. In addition, the thickness of the functional coating is too large, which affects the thickness uniformity of the functional coating and reduces the battery energy density of the lithium battery. The thickness of the functional coating is too small, which causes the poor lithium ion adsorption of the functional coating and reduces the battery energy density of the lithium battery.

[0068] In some embodiments, the functional coating further comprises a carbonized carbon material. For example, the carbonized carbon material may be graphite. Thus, the carbonized carbon material may increase the conductivity of the functional coating, thereby increasing the conductivity of the negative electrode current collector.

[0069] An embodiment of the present application provides a method for preparing a negative electrode current collector, the method comprising the following steps:

[0070] S100: mixing a current collector substrate, a carbon source solution and a metal organic framework material to obtain a mixture; a lithium-philic material is disposed on the surface of the metal organic framework material.

[0071] In this step, the current collector substrate, the carbon source solution and the metal organic framework material are mixed, and the carbon source solution and the metal organic framework material are distributed on the surface of the current collector substrate after mixing (for example, the carbon source solution and the zeolite imidazolate framework material are distributed on the surface of the current collector substrate after mixing).

[0072] In some embodiments, the mixing treatment includes: subjecting the current collector substrate, the carbon source solution, and the metal organic framework material to ultrasonic treatment, and filtering after standing (for example, filtering can be performed through anhydrous ethanol) to obtain a mixture; wherein the power of the ultrasonic treatment is 120W to 300W, and the ultrasonic treatment time is 1h to 3h. For example, the power of the ultrasonic treatment can be 120W, 150W, 200W, 250W, 300W, and the ultrasonic treatment time can be 1h, 1.5h, 2h, 2.5h, 3h.

[0073] The power and time of the ultrasonic treatment are controlled within the above range, the power and time of the ultrasonic treatment are moderate, the carbon source solution and the metal organic framework material are distributed on the current collector substrate with high uniformity, the lithium-philic material on the current collector substrate with high uniformity, and the current density in the subsequently prepared negative electrode current collector with high uniformity, which is beneficial to improve the uniformity of lithium deposition on the negative electrode current collector, thereby reducing the probability of nucleation and growth of lithium dendrites.

[0074] In some embodiments, the current collector substrate includes copper foam. In this way, the copper foam with a high surface area can increase the area where the lithium-philic material is set, and reduce the hidden danger of nucleation and growth of lithium dendrites due to uneven effective current density in the negative electrode current collector. In addition, the copper foam has a high surface area, which is conducive to adjusting the nucleation sites of lithium metal on the current collector substrate, shortening the mass transfer distance of lithium ions, improving the uniformity of lithium deposition on the negative electrode current collector prepared subsequently, and inhibiting the volume change of the negative electrode current collector.

[0075] In some embodiments, the carbon source solution includes at least one of glucose solution, ethylene glycol, glycerol and furfuryl alcohol. In this way, the carbon source solution is easy to obtain and inexpensive, which is conducive to reducing the cost of preparing the negative electrode current collector, and further conducive to achieving industrial production.

[0076] In some embodiments, the molar ratio of the carbon source solution to the metal organic framework material is (0.8-1.2): 1. For example, the molar ratio of the carbon source solution to the metal organic framework material can be 0.8:1, 0.85:1, 0.9:1, 0.95:1, 1.0:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1.

[0077] The molar ratio of the carbon source solution and the metal organic framework material is controlled within the above range, the ratio of the carbon source solution and the metal organic framework material is moderate, the prepared negative electrode current collector has better conductivity, the negative electrode current collector has better lithium precipitation effect, and the lithium battery has a higher battery energy density. In addition, it can alleviate the problem that the proportion of carbon source solution is too high and the metal organic framework material is too little, resulting in less lithium-philic material in the prepared negative electrode current collector and poor lithium precipitation effect of the negative electrode current collector, and it can also alleviate the problem that the proportion of metal organic framework material is too high and the carbon source solution is too little, resulting in poor conductivity of the prepared negative electrode current collector and poor battery energy density of the lithium battery.

[0078] In some embodiments, the method for preparing a zeolite imidazole ester framework material comprises: in a solvent, 2-methylimidazole and a metal source material (such as a zinc source material) are subjected to a coordination reaction to obtain a zeolite imidazole ester framework material. In this way, 2-methylimidazole and the metal source material (such as a zinc source material) have a good dispersion effect in the solvent, which is conducive to improving the effect of the coordination reaction of 2-methylimidazole and the metal source material (such as a zinc source material). In some possible embodiments, the above-mentioned solvent is deionized water.

[0079] In some embodiments, the method for preparing the zeolite imidazolate framework material comprises the following steps:

[0080] S110: adding 2-methylimidazole, a metal source material, and a dispersant into deionized water and stirring and mixing them to obtain a mixture containing a zeolite imidazole framework material.

[0081] In this step, 2-methylimidazole, metal source material, and dispersant are added to deionized water for stirring and mixing. The dispersant can promote the good dispersion of 2-methylimidazole and metal source material in deionized water, which is beneficial to improve the effect of the coordination reaction between 2-methylimidazole and metal source material. Among them, the dispersant can be freely selected according to actual conditions, and the embodiment of the present application is not limited here.

[0082] In some embodiments, the molar ratio of 2-methylimidazole to the metal source material is (0.8-1.2):(0.8-1.2). For example, the molar ratio of 2-methylimidazole to the metal source material can be 0.8:0.8, 1:0.8, 1.2:0.8, 1:0.8, 1:1, 1:1.2, 1.2:0.8, 1.2:1, 1.2:1.2. The molar ratio of the above-mentioned 2-methylimidazole to the metal source material is controlled within the above-mentioned range, and the mixing effect of 2-methylimidazole and the metal source material is better, which is conducive to obtaining a zeolite imidazole ester framework material with better binding strength.

[0083] In some embodiments, during the above stirring and mixing process, the pH of the mixture containing the zeolite imidazolate framework material can be detected. When the pH of the mixture containing the zeolite imidazolate framework material is stable, it proves that the coordination reaction between 2-methylimidazole and the metal source material is basically completed. The reason is that the 2-methylimidazole solution is alkaline, and when the reaction is complete, the pH value of the mixture containing the zeolite imidazolate framework material reaches a stable value.

[0084] In some embodiments, the metal source material may be at least one of a zinc source material, a silver source material, a magnesium source material, an aluminum source material, and a tin source material. In some possible embodiments, the silver source material includes silver nitrate. In some possible embodiments, the magnesium source material includes magnesium nitrate. In some possible embodiments, the aluminum source material includes aluminum nitrate. In some possible embodiments, the tin source material includes tin nitrate.

[0085] In some possible embodiments, the zinc source material includes at least one of zinc nitrate hexahydrate and zinc acetate dihydrate. In this way, zinc nitrate hexahydrate and zinc acetate dihydrate can provide zinc ions (Zn) with good lithium affinity. 2+), in addition, the zinc source material is easy to obtain and low in price, which is conducive to reducing the cost of preparing the negative electrode current collector, and thus is conducive to industrial production. In some possible embodiments, the dispersant includes at least one of N,N-dimethylformamide (DMF), ethylene glycol, and methanol. In this way, 2-methylimidazole and the zinc source material can be dispersed in deionized water by the above dispersant. In addition, the dispersant is easy to obtain and low in price, which is conducive to reducing the cost of preparing the negative electrode current collector, and thus is conducive to industrial production.

[0086] S120: Cleaning the mixture containing the zeolite imidazolate framework material to obtain the zeolite imidazolate framework material.

[0087] In this step, by cleaning the mixture containing zeolite imidazolate skeleton material, the impurities in the mixture containing zeolite imidazolate skeleton material can be removed to obtain zeolite imidazolate skeleton material (the shape of zeolite imidazolate skeleton material can be white powder). Like this, the method for preparing zeolite imidazolate skeleton material is simple and easy, productive rate is higher, and the average grain size of the zeolite imidazolate skeleton material prepared is less, which is conducive to the subsequent zeolite imidazolate skeleton material being evenly arranged on the surface of the current collector substrate.

[0088] In some embodiments, the cleaning process includes: allowing the mixture containing the zeolite imidazolate framework material to stand (the standing temperature can be room temperature) to obtain a sedimentation layer, and washing the sedimentation layer to obtain the zeolite imidazolate framework material; in this way, by allowing the mixture containing the zeolite imidazolate framework material to stand, most of the liquid in the mixture containing the zeolite imidazolate framework material can be removed to obtain a sedimentation layer enriched with the zeolite imidazolate framework material; washing the sedimentation layer can remove impurities in the sedimentation layer enriched with the zeolite imidazolate framework material to obtain the zeolite imidazolate framework material. For example, the cleaning process includes: centrifuging, washing, and drying the sedimentation layer in sequence to obtain the zeolite imidazolate framework material.

[0089] S200: heat-treating the mixture to obtain a negative electrode current collector.

[0090] In this step, by heat treating the mixture, the carbon source solution and the metal organic framework material will be carbonized, which can improve the conductivity, stability and mechanical strength of the negative electrode current collector. The negative electrode current collector includes a current collector substrate and a functional coating arranged on the current collector substrate, the functional coating includes a carbonized metal organic framework material and a carbonized carbon material, and the surface of the metal organic framework material is provided with a lithium-philic material; the carbonized carbon material is conducive to improving the conductive effect of the negative electrode current collector.

[0091] In some embodiments, the conditions of the heat treatment are: the temperature of the heat treatment is 350°C to 650°C, and the time of the heat treatment is 2h to 5h. For example, the temperature of the heat treatment can be 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, and the time of the heat treatment can be 2h, 3h, 4h, 5h. The temperature and time of the above-mentioned heat treatment are controlled within the above-mentioned range, the temperature and time of the heat treatment are moderate, the degree and rate of carbonization of the carbon source solution and the metal organic framework material are better, and the negative electrode current collector has better conductivity, stability and mechanical strength.

[0092] In some embodiments, the heat treatment is performed under an inert gas atmosphere, wherein the inert gas forming the inert gas atmosphere may be argon.

[0093] The embodiment of the present application provides a negative electrode sheet, which includes the negative electrode current collector described above, or the negative electrode current collector prepared by the method for preparing the negative electrode current collector described above. In this way, the negative electrode sheet has excellent safety, as well as high chemical stability, mechanical strength, thermal stability, and conductivity.

[0094] The embodiment of the present application provides a solid-state lithium battery, which includes a positive electrode sheet, a solid electrolyte membrane, and the above-mentioned negative electrode sheet, and the solid electrolyte membrane is located between the positive electrode sheet and the negative electrode sheet. In this way, the solid-state lithium battery has excellent safety, as well as good electrochemical performance, mechanical strength, operating temperature range, and battery energy density.

[0095] In some embodiments, the positive electrode sheet includes a positive electrode active material, a solid electrolyte, a conductive agent, and a binder. In some possible embodiments, the positive electrode active material includes LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.4 Co 0.2 Mn 0.4 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2 and LiNi 0.8 Co 0.1 Mn 0.1 In some possible embodiments, the solid electrolyte includes Li 10 GeP2S 12 、Li3PS4、Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5, Li6PS5Br and Li6PS5I. In some possible embodiments, the conductive agent includes at least one of conductive graphite, conductive carbon black, carbon nanotubes and graphene. In some possible embodiments, the binder is selected from at least one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). In some possible embodiments, the mass ratio of the positive active material, the solid electrolyte, the conductive agent and the binder is (65%-80%): (10%-25%): (1%-3%): (1%-2%).

[0096] In some embodiments, in a solid-state lithium battery, the material of the solid electrolyte membrane between the positive electrode sheet and the negative electrode sheet includes Li 10 GeP2S 12 、Li3PS4、Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 , Li6PS5Br and Li6PS5I.

[0097] In some embodiments, a method for preparing a solid-state lithium battery is provided, comprising the following steps: dispersing a precursor solution of a solid electrolyte in an organic solvent (for example, the organic solvent may be at least one of acetonitrile, tetrahydrofuran, toluene, n-heptane, xylene, and anisole) to form a dispersion, coating the dispersion on an electrolyte diaphragm, and drying after coating to obtain a solid electrolyte membrane; assembling the positive electrode sheet, the electrolyte membrane layer, and the negative electrode sheet in a stacked manner, and performing cold isostatic pressing to obtain an all-solid-state lithium battery. Among them, cold isostatic pressing has the advantages of uniform pressure and the battery core is not easily deformed, and can achieve a good combination between the positive electrode sheet, the electrolyte membrane layer, and the negative electrode sheet.

[0098] In some possible embodiments, the pressure of cold isostatic pressing is 400 MPa to 500 MPa. For example, the pressure of cold isostatic pressing can be 400 MPa, 420 MPa, 440 MPa, 460 MPa, 480 MPa and 500 MPa. Controlling the pressure of cold isostatic pressing within the above range is conducive to ensuring uniform pressure of the all-solid-state lithium battery, the battery cell is not easily deformed, and sufficient contact between the positive electrode sheet, the electrolyte membrane layer and the negative electrode sheet can be achieved.

[0099] The embodiment of the present application provides a vehicle, which includes the solid-state lithium battery of the above embodiment. In this way, the vehicle has higher safety and longer service life.

[0100] The following describes the embodiments of the present application. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.

[0101] Example 1

[0102] 1. Prepare the negative electrode of solid-state lithium battery.

[0103] (1-1) adding 2-methylimidazole, N,N-dimethylformamide (DMF) and zinc nitrate hexahydrate (Zn(NO3)2·6H2O) to deionized water and stirring to fully dissolve them; during the above stirring and mixing process, detecting the pH of the mixture containing the zeolite imidazolate framework material, and stopping stirring when the pH of the mixture containing the zeolite imidazolate framework material is stable, to obtain a mixture containing the zeolite imidazolate framework material; wherein the feeding amounts of 2-methylimidazole, N,N-dimethylformamide and zinc nitrate hexahydrate are 0.001 mol, 0.3 mol and 0.001 mol, respectively;

[0104] (1-2) allowing the mixture containing the zeolite imidazolate framework material obtained in step (1-1) to stand to obtain a sedimentation layer, and sequentially centrifuging, washing, and drying the sedimentation layer to obtain the zeolite imidazolate framework material (ZIF-8);

[0105] (1-3) subjecting the copper foam, the glucose solution (with a concentration of 0.5 mol / L), and the zeolite imidazolate framework material obtained in step (1-2) to ultrasonic treatment, and filtering with anhydrous ethanol after standing to obtain a mixture; wherein the feeding amounts of the glucose solution and the zeolite imidazolate framework material are 0.001 mol and 0.001 mol, respectively, the ultrasonic treatment power is 200 W, and the ultrasonic treatment time is 3 h;

[0106] (1-4) Under an argon atmosphere, heat-treating the mixture obtained in step (1-3) to obtain a negative electrode current collector, wherein the negative electrode current collector includes a functional coating, and the functional coating includes a carbonized zeolite imidazolate framework material and a carbonized carbon material; wherein the heat treatment conditions are: heating to 500° C. at a heating rate of 3° C. / min and then keeping the temperature for 5 hours. The negative electrode current collector is used as the negative electrode of a solid-state lithium battery.

[0107] 2. Prepare the positive electrode of solid-state lithium battery.

[0108] The positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), conductive agent (conductive graphite) and solid electrolyte (Li10 GeP2S 12 ) is mixed into a solvent (NMP) to form a positive electrode sheet slurry; the above positive electrode sheet slurry is coated on the positive electrode collector (copper foil) to obtain a positive electrode sheet; wherein the masses of the positive electrode active material, the solid electrolyte and the conductive agent are 8.2 mg, 2 mg and 1.5 mg respectively.

[0109] 3. Prepare solid electrolyte membrane.

[0110] The solid electrolyte precursor solution is dispersed in acetonitrile to form a dispersion, and the dispersion is coated on the electrolyte separator, and then dried to obtain a solid electrolyte membrane; the material of the solid electrolyte membrane is Li 10 GeP2S 12 .

[0111] 4. Prepare solid-state lithium batteries.

[0112] The positive electrode sheet, the electrolyte membrane layer and the negative electrode sheet are assembled in a stacking manner and cold isostatically pressed to obtain an all-solid-state lithium battery, wherein the cold isostatic pressing pressure is 450 MPa.

[0113] Example 2

[0114] The difference between Example 2 and Example 1 is:

[0115] In step (1-1), zinc nitrate hexahydrate is replaced with zinc acetate dihydrate;

[0116] The feed amounts of 2-methylimidazole, N,N-dimethylformamide and zinc nitrate hexahydrate are 0.0009 mol, 0.3 mol and 0.001 mol respectively.

[0117] Example 3

[0118] The difference between Example 3 and Example 1 is that:

[0119] In step (1-3), glucose is replaced by ethylene glycol (concentration is 0.5 mol / L); the feeding amounts of ethylene glycol and zeolite imidazolate framework material are 0.0008 mol and 0.001 mol respectively.

[0120] Example 4

[0121] The difference between Example 4 and Example 1 is:

[0122] In step (1-3), glucose is replaced by glycerol (concentration is 0.5 mol / L); the feeding amounts of glycerol and zeolite imidazolate framework material are 0.0009 mol and 0.001 mol respectively.

[0123] Example 5

[0124] The difference between Example 5 and Example 1 is:

[0125] In step (1-3), glucose is replaced by furfuryl alcohol (concentration is 0.5 mol / L); the feeding amounts of glycerol and zeolite imidazolate framework material are 0.0008 mol and 0.001 mol respectively.

[0126] Example 6

[0127] The difference between Example 6 and Example 1 is:

[0128] In step (1-4), the heat treatment conditions are: heating to 550°C at a heating rate of 3°C / min and then keeping the temperature for 5 hours.

[0129] Example 7

[0130] The difference between Example 7 and Example 1 is:

[0131] In step (1-4), the heat treatment conditions are: heating to 600°C at a heating rate of 3°C / min and then keeping the temperature for 5 hours.

[0132] Example 8

[0133] The difference between Example 8 and Example 1 is:

[0134] (1-3) adding the copper foam and the zeolite imidazole ester framework material obtained in step (1-2) to 30 ml of deionized water for ultrasonic treatment, and filtering with anhydrous ethanol after standing to obtain a mixture; the power of the ultrasonic treatment is 300 W, and the time of the ultrasonic treatment is 3 hours;

[0135] (1-4) Under an argon atmosphere, heat-treating the mixture obtained in step (1-3) to obtain a negative electrode current collector, wherein the negative electrode current collector includes a functional coating, and the functional coating only includes a carbonized zeolite imidazolate framework material; wherein the heat treatment conditions are: heating to 500° C. at a heating rate of 3° C. / min and then keeping the temperature for 5 hours. The negative electrode current collector is used as the negative electrode of a solid-state lithium battery.

[0136] Example 9

[0137] The difference between Example 9 and Example 1 is:

[0138] In step (1-1), zinc nitrate hexahydrate (zinc source material) is replaced with silver nitrate (silver source material).

[0139] Example 10

[0140] The difference between Example 10 and Example 1 is:

[0141] In step (1-1), zinc nitrate hexahydrate (zinc source material) is replaced with magnesium nitrate (magnesium source material).

[0142] Embodiment 11

[0143] The difference between Example 11 and Example 1 is that:

[0144] In step (1-1), zinc nitrate hexahydrate (zinc source material) is replaced with aluminum nitrate (aluminum source material).

[0145] Example 12

[0146] The difference between Example 12 and Example 1 is:

[0147] In step (1-1), zinc nitrate hexahydrate (zinc source material) is replaced with tin nitrate (tin source material).

[0148] Comparative Example 1

[0149] The difference between Comparative Example 1 and Example 1 is:

[0150] Copper foam is used alone as the negative electrode current collector.

[0151] Performance Testing

[0152] The negative electrode sheets and solid-state lithium batteries obtained in Examples 1-12 and Comparative Example 1 were tested.

[0153] (1) Energy density test of solid-state lithium battery:

[0154] At 25°C, the solid-state lithium batteries of Examples 1-12 and Comparative Example 1 were charged to 4.35V at 1C constant current, charged to 0.05C at constant voltage, and discharged to 2.5V at 1C constant current, which was a charge and discharge cycle. The solid-state lithium battery was charged and discharged 10 times in this way, and the energy density of the battery was obtained by dividing the discharge energy of the 10th cycle by the total weight of the battery.

[0155] (2) Width test of operating temperature of solid-state lithium batteries:

[0156] Working temperature tests were performed on Examples 1-12 and Comparative Example 1 in a temperature range of -10°C to 50°C at intervals of 5°C. The solid-state lithium battery was charged to 4.35V at 1C constant current, charged to 0.05C at constant voltage, and discharged to 2.5V at 1C constant current, which was a charge and discharge cycle. After the solid-state lithium battery was cycled 10 times, the upper and lower temperature limits at which the capacity retention rate was 80% were the width of the working temperature of the solid-state lithium battery.

[0157] (3) Service life of solid-state lithium batteries:

[0158] At 25°C, the solid-state lithium batteries of Examples 1-12 and Comparative Example 1 were charged to 4.35V at 1C constant current, charged to 0.05C at constant voltage, and discharged to 2.5V at 1C constant current, which was a charge and discharge cycle. The solid-state lithium battery was charged and discharged in this way. When the capacity decayed to 70% of the initial capacity, the number of cycles obtained at this moment was the service life of the solid-state lithium battery.

[0159] Important parameters for preparing the negative electrode current collector are shown in Table 1; the negative electrode sheets and solid-state lithium batteries of Examples 1-8 and Comparative Example 1 were tested, and the test results are shown in Table 2.

[0160] Table 1

[0161]

[0162] Table 2

[0163]

[0164] Analyze the data in Table 1 and Table 2:

[0165] Compared to Comparative Example 1, the negative electrode current collector prepared by the method provided in Examples 1-8 of the present application has a lithium-philic material (zinc ion), and the negative electrode current collector has a higher uniformity of lithium deposition, so that the lithium battery has better safety and battery energy density. In addition, since the carbonized metal organic framework material has better chemical stability, mechanical strength, thermal stability, and conductivity, the chemical stability, mechanical strength, thermal stability, and conductivity of the negative electrode current collector can be correspondingly improved, and the electrochemical performance, mechanical strength, operating temperature width, and battery energy density of the lithium battery can be correspondingly improved. Compared to Example 8, the negative electrode current collector prepared in Examples 1-7 includes a carbonized carbon material, which has a higher conductivity, and the relative lithium battery has an excellent battery energy density.

[0166] In addition, the negative electrode current collector prepared by the method provided in Examples 9-12 of the present application also has a high uniformity of lithium deposition, which makes the lithium battery have better safety and battery energy density. The lithium battery also has good electrochemical properties, mechanical strength, operating temperature range, and battery energy density.

[0167] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A negative electrode current collector, characterized in that: include: a current collector substrate; A functional coating is disposed on at least a portion of the surface of the current collector substrate, wherein the functional coating comprises a carbonized metal organic framework material, and a lithium-philic material is disposed on the surface of the metal organic framework material.

2. The negative electrode current collector according to claim 1, characterized in that: The metal organic framework material comprises a zeolite imidazolate framework material, the zeolite imidazolate framework material comprises coordinated imidazolate ions and lithium-philic metal ions, and the lithium-philic material comprises the lithium-philic metal ions.

3. The negative electrode current collector according to claim 2, characterized in that: The lithium-philic metal ions include at least one of zinc ions, silver ions, magnesium ions, aluminum ions and tin ions.

4. The negative electrode current collector according to claim 1, characterized in that: The current collector substrate includes copper foam.

5. The negative electrode current collector according to claim 1, characterized in that: The pore diameter of the metal organic framework material is 0.5 nanometers to 1.2 nanometers.

6. The negative electrode current collector according to any one of claims 1 to 5, characterized in that: The thickness of the functional coating is 0.3 micrometer to 0.8 micrometer.

7. The negative electrode current collector according to any one of claims 1 to 5, characterized in that: The functional coating also includes carbonized carbon material.

8. A method for preparing a negative electrode current collector, characterized in that: include: The current collector substrate, the metal organic framework material and the carbon source solution are mixed to obtain a mixture; heat treating the mixture to obtain a negative electrode current collector; Wherein, a lithium-philic material is arranged on the surface of the metal organic framework material.

9. The method according to claim 8, characterized in that The mixing process satisfies at least one of the following conditions: The current collector substrate comprises copper foam; The metal organic framework material comprises a zeolite imidazolate framework material, and the lithium-philic material comprises a lithium-philic metal ion in the zeolite imidazolate framework material; The carbon source solution comprises at least one of glucose solution, ethylene glycol, glycerol and furfuryl alcohol; The feeding molar ratio of the carbon source solution and the metal organic framework material is (0.8-1.2):

1.

10. The method according to claim 9, characterized in that The method for preparing the zeolite imidazolate framework material comprises: in a solvent, carrying out coordination reaction between 2-methylimidazole and a metal source material to obtain the zeolite imidazolate framework material.

11. The method according to claim 10, characterized in that The feeding molar ratio of the 2-methylimidazole to the metal source material is (0.8-1.2):(0.8-1.2).

12. A negative electrode plate, characterized in that: The negative electrode current collector comprises the negative electrode current collector according to any one of claims 1 to 7, or the negative electrode current collector prepared by the method according to any one of claims 8 to 11.

13. A solid-state lithium battery, characterized in that: It comprises a positive electrode sheet, a solid electrolyte membrane, and the negative electrode sheet as claimed in claim 12, wherein the solid electrolyte membrane is located between the positive electrode sheet and the negative electrode sheet.

14. A vehicle, characterized in that: Including the solid-state lithium battery as described in claim 13.

Citation Information

Cited By

  • Functional current collector for improving thermal stability, preparation method thereof, pole piece and battery

    CN121123291A